Melanocortin 5 receptor activates ERK1/2 through a PI3K-regulated signaling mechanism - Rodrigues, AR (2009)
Melanocortin 5 receptor (MC5R) is a G protein coupled receptor (GPCR) with high affinity for alpha-melanocyte-stimulating hormone (alpha-MSH). To unravel some of the downstream cell-signaling pathways activated by this receptor, HEK293 cells were transiently and stably transfected with a vector encoding green fluorescent protein (GFP)-tagged MC5R. In these cells the receptor was correctly addressed to the cell Surface and was functional, as shown by the MC5R-induced formation of intracellular cAMP. In fact, the MC5R agonist alpha-MSH induced a 10- or 16-fold increase (transient or stable cells, respectively) above the cAMP levels found in unstimulated cells. Moreover, in cells stably expressing MC5R-GFP, a-MSH promoted ERK1/2 phosphorylation in a dose-dependent manner (EC50 = 7.3 nM) with the maximal effect occurring after 5 min of agonist incubation. The signaling pathway conveyed through ERK1/2 is not linked to cAMP, since the phosphorylation of these kinases is unchanged by the inhibition of adenylyl cyclase. Also, ERK1/2 activation is not significantly affected by protein kinase A (PKA), protein kinase C (PKC) and protein kinase B or Akt (Akt/PKB) specific inhibitors. However, alpha-MSH-induced ERK1/2 activation is abolished by the phosphatidylinositol 3-kinase (PI3K) inhibitors wortmannin and LY294002. Altogether, these findings demonstrate that MC5R signals through a PIA-regulated Akt-independent pathway leading to downstream activation of ERK1/2. The involvement of these MAPK suggests that MC5R could be implicated in cellular proliferation or differentiation mechanisms.